Actuality of Alash people’s Ideas About Independence - Yertassova Г.Қ.; Sak Қ.Ө. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
A distinctive feature and uniqueness of the free Kazakhstan is its history. The history of today where every day brought a fight for freedom and independence. A bright, fiery period of this story, without fail, is the story of Alash. Alash summoned the people to unite. Alash is a bright page where the Kazakh society witnessed a renewal, bold quests, a search for education and science, as well as risks and truth. The idea of Alash was formed at the beginning of the XX century as a national-state idea of the Kazakh people. It can be noted that the Alash idea became the fundament of the Kazakh nationality. The colonial policy of Russia in the XIX century caused the emergence of fighters and national patriots who loved their Motherland. This regime made a purpose to open as many Russian-Kazakh schools in the vast Kazakh land as possible and influence the national intelligentsia. In turn, the democratic national intelligentsia acted on behalf of the Kazakh people. It fought for its independence and for the way to gain freedom from the colonial pressure. It was for these purposes that Alash activists in 1905 stepped up in terms of political work. As a result, the Alash party was founded. On the historical stage, the national intelligentsia was formed. The Alashordа party which was formed in 1917, as well as the historical activities of the national intelligentsia of the Alash society made it into history on the path to the formation of an independent state. The main objectives of the Alash movement were: self-government of the Kazakh people and recognition of the metropolis in the formation of the state system that could protect its national interests, the formation in the end of a free, independent state, limit the relocation from Russia to the Kazakh lands, develop livestock using the best world experience, start market relations, establish democratic principles and respect personal rights of a person, systematize education and language development.